Performance of starfruit cv. B10 under netted structure. II. Effect of crop load on exportable yield, fruit size, fruit physical and chemical properties - Mahmood, Zabedah; Abdullah, Mohd Yusoff; Abd Halim, Mohd Ridzwan; Hassan, Siti Aishah; Ramlan, Mohd Fauzi (Malaysian Agricultural Research and Development Institute (MARDI), 2008)
Exportable yield and fruit size of starfruit at several crop loads under netted structure were studied in the starfruit farm at MARDI, Serdang, Selangor. Increase in crop load resulted in increase in number of small (S) and medium (M) size fruits. The exportable yield also increased from 50% at the lower crop load to 75% at the high crop load (p <0.05). The number of exportable S and M increased from 1 box/tree at the low crop load to 13 boxes/tree and 7–8 boxes/tree respectively at the highest crop load (p <0.05). Very small fruits (VS) and extra large fruits (XL) which constitute as reject fruits were significantly influenced by the crop load treatments. The number of VS fruit reached 141 fruits/tree at the highest crop load. A reverse trend was found for the number of XL fruits/tree. Fruit density and fruit firmness were not significantly influenced by the crop load treatments. The fruits of the low crop load had significantly higher wing tip thickness (p <0.05). Fruits of the lowest crop load had the highest width of wing base (p <0.05). However, vitamin C and total soluble solid content were not significantly influenced by the crop load treatments.